A rapid detection method for calcium chloride concentration based on localized surface plasmon resonance
Through the rapid detection method based on local surface plasmon resonance, the existing calcium chloride detection methods are solved, and the rapid and accurate detection of calcium chloride concentration is achieved, and the on-site detection in multiple fields is suitable for field testing in multiple fields. .
Patent Information
- Application Number
- CN202411649145.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-19
AI Technical Summary
The existing calcium chloride detection methods are cumbersome to operate, have long detection time, many interfering elements, insufficient sensitivity and specificity, making it difficult to meet the needs of rapid on-site detection.
Using a rapid detection method based on local surface plasmon resonance (LSPR), the absorbance data of calcium chloride solution was measured by preparing LSPR sensors and using an ultraviolet spectrophotometer, and the calcium chloride concentration was calculated according to the standard curve.
It realizes rapid and accurate detection of calcium chloride concentration, with the advantages of simple operation, short response time, high sensitivity and low cost, and is suitable for on-site rapid detection in food safety, chemical production, environmental monitoring and other fields.
Smart Images

Figure CN119147506B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a rapid detection method for calcium chloride concentration based on localized surface plasmon resonance, and belongs to the technical field of chemical analysis. Background Art
[0002] Calcium chloride is a commonly used inorganic salt and an important chemical material. It is widely used in various industrial, agricultural and food fields, such as ice and snow melting agents, food additives, water treatment chemicals and chemical fiber additives.
[0003] In terms of chemical fiber additives, calcium chloride can be used as a softener because it can promote the expansion of the gaps between fiber molecules, increase the softness of the fiber, and avoid fiber beading. Calcium chloride can also enhance the mutual adsorption between fiber and dye, and also promote the uniform distribution of dye inside the fiber. During the processing of textiles, fibers may be damaged by stretching or friction. In this case, calcium chloride can help the fibers recover, increase fiber strength, and extend the service life of textiles. In addition, calcium chloride has several other applications. For example, it can be used as a fiber protector. After the fiber is slightly soaked in calcium chloride, the fiber can prevent the generation of odor and also play a role in mildew protection. However, the concentration of calcium chloride solution will also affect its application effect. Therefore, in industrial production and scientific research, accurate and rapid detection of the concentration of calcium chloride solution is crucial.
[0004] Traditional calcium chloride detection methods usually include ion selective electrode method, EDTA titration method, etc. These methods have the disadvantages of cumbersome operation, long detection time, many interfering elements, low sensitivity and specificity, and are not suitable for rapid on-site detection. Therefore, it is particularly urgent to develop a fast, convenient and accurate detection method. Summary of the invention
[0005] The invention aims at the deficiencies in the prior art and provides a method for rapid detection of calcium chloride concentration based on localized surface plasmon resonance. The detection method can realize on-site, real-time, rapid and accurate detection of the concentration of a calcium chloride solution.
[0006] The technical solution of the present invention to solve the above technical problems is as follows: a rapid detection method for calcium chloride concentration based on localized surface plasmon resonance, the detection method is:
[0007] S1. Preparation of LSPR sensor:
[0008] The clean FTO substrate is placed in a modification solution for soaking, and after the soaking, the chemically modified FTO substrate is obtained by washing and drying; wherein the modification solution is an ethanol solution containing a thiol and a ligand compound, and the ligand compound is any one of cyclodextrin, crown ether, and ethylenediaminetetraacetic acid;
[0009] The LSPR sensor is obtained by assembling metal nanoplates on the surface of a chemically modified FTO substrate using a photoelectric induced deposition method;
[0010] S2. Detection of calcium chloride concentration:
[0011] The calcium chloride solution sample to be tested is evenly coated on the surface of the LSPR sensor, an ultraviolet spectrophotometer is used to measure the absorbance data of the sample on the surface of the LSPR sensor, and then the calcium chloride concentration of the calcium chloride solution sample to be tested is calculated according to the standard curve.
[0012] Furthermore, in step S1, in the modified solution, the concentration of thiol is 2-10 mM, and the concentration of ligand compound is 1-5 mM.
[0013] Furthermore, in step S1, in the photoelectric induced deposition method, the light source used is a xenon lamp, and the light induction distance is 25-35 cm.
[0014] Furthermore, in step S1, in the photoelectric induced deposition method, the current density of the electrodeposition is 5-10 mA / cm 2 .
[0015] Furthermore, in step S1, the material of the metal nanoplate is gold, silver or copper, and the thickness of the metal nanoplate is 25-35 nm.
[0016] Furthermore, in step S1, in the photoelectric induced deposition method, the electrolyte used is HAuCl4 aqueous solution, AgNO3 aqueous solution or Cu(NO3)2 aqueous solution, and the concentration of the electrolyte is 0.04-0.05M.
[0017] Furthermore, the pH of the electrolyte is 4-5, and the temperature of the electrolyte is 60-80°C.
[0018] Furthermore, in step S2, when the localized surface plasmon resonance spectrometer performs detection, the absorbance of the sample to be tested is measured at a wavelength of 520 nm.
[0019] Furthermore, in step S1, the clean FTO substrate is treated by washing the FTO substrate with acetone, isopropanol and ultrapure water for at least 30 minutes each, then drying with N2 gas, and drying in an oven for at least 120 minutes to obtain a clean FTO substrate.
[0020] Furthermore, in step S1, the clean FTO substrate is soaked in the modification solution for 12-24 hours. After the soaking, it is washed with ethanol and dried in a N2 atmosphere to obtain a chemically modified FTO substrate.
[0021] The beneficial effects of the present invention are:
[0022] The rapid detection method based on localized surface plasmon resonance (LSPR) of the present invention can realize rapid and accurate detection of liquid calcium chloride concentration, has the advantages of simple operation, short response time, high sensitivity, low cost, etc., and does not require complicated sample pretreatment, has high specificity and repeatability, and is suitable for on-site rapid detection in multiple fields such as food safety, chemical production, and environmental monitoring.
[0023] The present invention measures the content of calcium chloride in industrial calcium chloride by introducing LSPR and ultraviolet spectrophotometry, which not only achieves the technical effects of anti-interference, accurate and rapid analysis, but also has a measurement range greater than the national standard. The EDTA measurement method in the national standard has a test range of 12-40%, and the measurement range of the detection method is expanded to 5%-50%, overcoming the shortcomings of the traditional EDTA measurement method. The method of the present invention realizes the rapid determination of the content of calcium chloride in industrial liquid calcium chloride, can provide accurate analysis data for the production process in a timely manner, is simple, rapid, easy to operate, and has high accuracy, and can meet the needs of rapid analysis and detection of the content of industrial liquid calcium chloride.
[0024] The detection method of the present invention, by reasonably selecting the process conditions for preparing the LSPR sensor, enables the LSPR spectrum detection technology to realize rapid and accurate detection of the calcium chloride concentration. Compared with the existing chemical detection method, the calcium chloride concentration error does not exceed ±0.12%. Moreover, the detection method of the present invention can effectively reduce manual errors and improve detection efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 Schematic diagram for preparing LSPR sensor;
[0026] Figure 2 It is the standard curve diagram of Example 2;
[0027] In the figure, 1. light source generator; 2. light source; 3. sample preparation cell; 4. platinum sheet; 5. FTO substrate; 6. electrolytic cell; 7. Ag / AgCl electrode. DETAILED DESCRIPTION
[0028] The specific implementation of the present invention is described in detail below. The present invention can be implemented in many other ways than those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed.
[0029] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used are only for describing specific embodiments and are not intended to limit the present invention.
[0030] A rapid detection method for calcium chloride concentration based on localized surface plasmon resonance, the detection method comprising:
[0031] S1. Preparation of LSPR sensor:
[0032] The clean FTO substrate is placed in a modified solution for soaking. After the soaking, the chemically modified FTO substrate is obtained by washing and drying. The metal is assembled on the FTO substrate by using the photoelectric induced deposition method. The FTO substrate has a certain conductivity, which can adjust the LSPR wavelength to be close to the infrared wavelength range, and can also improve the LSPR spectrum intensity and detection sensitivity.
[0033] The LSPR sensor is obtained by assembling metal nanoplates on the surface of a chemically modified FTO substrate using a photoelectric induced deposition method;
[0034] S2. Detection of calcium chloride concentration:
[0035] The calcium chloride solution sample to be tested is uniformly coated on the surface of the LSPR sensor (in specific operation, the amount of sample coated for each batch of testing is the same), and the absorbance data of the sample on the surface of the LSPR sensor is measured using an ultraviolet spectrophotometer. The concentration of the sample to be tested is determined according to the change in the LSPR spectral response, and the position and intensity of the absorption peak are recorded; the absorption peak displacement caused by calcium chloride is analyzed by comparing the LSPR spectrum of the control sample (solution without calcium chloride), and the calcium chloride concentration is calculated in combination with the standard curve.
[0036] Specifically, in step S1, the modified solution is an ethanol solution containing thiol and a ligand compound, and the ligand compound is a cyclodextrin containing multiple hydroxyl groups and capable of encapsulating Ca 2+ Crown ethers, which can react with Ca 2+ Any one of the ethylenediaminetetraacetic acid compounds that forms a stable complex; chemically modifying the FTO substrate surface using a ligand compound is more conducive to recognizing calcium chloride.
[0037] Specifically, in step S1, in the modified solution, the concentration of thiol is 2-10 mM, and the concentration of ligand compound is 1-5 mM.
[0038] Specifically, in step S1, in the photoelectric induced deposition method, the light source used is a xenon lamp, and the light induction distance is 25-35 cm.
[0039] Specifically, in step S1, in the photoelectric induced deposition method, the current density of the electrodeposition is 5-10 mA / cm 2 .
[0040] Specifically, in step S1, the material of the metal nanoplate is gold, silver or copper, and the thickness of the metal nanoplate is 25-35 nm.
[0041] More specifically, the thickness of the metal nanoplate in the embodiment of the present invention is 30 nm.
[0042] Specifically, in step S1, in the photoelectric induced deposition method, the electrolyte used is HAuCl4 aqueous solution, AgNO3 aqueous solution or Cu(NO3)2 aqueous solution, and the concentration of the electrolyte is 0.04-0.05M.
[0043] Specifically, the pH of the electrolyte is 4-5 (dilute hydrochloric acid solution can be used to adjust the pH to 4-5), and the temperature of the electrolyte is 60-80°C.
[0044] Specifically, in step S2, when the localized surface plasmon resonance spectrometer performs detection, the absorbance of the sample to be tested is measured at a wavelength of 520 nm.
[0045] Specifically, in step S1, the treatment method of the clean FTO substrate is: the FTO substrate is cleaned with acetone, isopropanol and ultrapure water for at least 30 minutes each, then dried with N2 gas, and then placed in an oven at 60°C for at least 120 minutes to obtain a clean FTO substrate.
[0046] Specifically, in step S1, the clean FTO substrate is soaked in the modification solution for 12-24 hours. After the soaking, it is washed with ethanol and dried in a N2 atmosphere to obtain a chemically modified FTO substrate.
[0047] More specifically, when preparing the LSPR sensor, Figure 1 As shown, the sample preparation pool 3 (single-type H cell) is provided with an electrolytic cell 6, a platinum sheet 4 and an Ag / AgCl electrode 7, the electrolytic cell 6 is filled with an electrolyte, the platinum sheet 4 and the Ag / AgCl electrode 7 serve as electrodes, the FTO substrate 5 is placed in the electrolyte, the light source generator 1 enables the light source 2 to emit light to irradiate the FTO substrate 5, and a photoelectric induced deposition method is used to form a metal nanoplate on the FTO substrate 5.
[0048] More specifically, the method for establishing a standard curve is as follows: accurately weigh calcium chloride, prepare a standard sample of a calcium chloride aqueous solution with a concentration of 5%-50%, and evenly apply the standard samples of calcium chloride aqueous solutions of various concentrations on the surface of the LSPR sensor. Use an ultraviolet spectrophotometer to measure the absorbance data of the standard sample on the surface of the LSPR sensor at 520nm, and draw a standard curve with absorbance as the ordinate and the calcium chloride concentration of the standard sample as the abscissa.
[0049] Example 1
[0050] S1. Preparation of LSPR sensor:
[0051] (1-1) Cleaning of FTO substrate: The FTO substrate was cleaned with acetone, isopropanol and ultrapure water for 30 min each, then dried with N2 gas and placed in an oven for 120 min to obtain a clean FTO substrate.
[0052] (1-2) Preparation of modification solution: Dissolve thiol and ethylenediaminetetraacetic acid in ethanol to obtain a modification solution, wherein the concentration of thiol in the modification solution is 2 mM, and the concentration of crown ether in the modification solution is 2 mM.
[0053] (1-3) Chemical modification of FTO substrate: The clean FTO substrate was immersed in the modification solution for 12 h. After being taken out, it was washed with ethanol and dried in a N2 atmosphere to obtain the chemically modified FTO substrate.
[0054] (1-4) Assembly of gold nanoplates: The chemically modified FTO substrate was placed in an electrolyte (HAuCl4 aqueous solution with a concentration of 0.05 M), and the metal nanoplates were assembled on the surface of the chemically modified FTO substrate by photoelectric induced deposition to obtain the LSPR sensor, wherein the distance between the xenon lamp and the FTO substrate was 30 cm, and the current density of the electrodeposition was 10 mA / cm 2 , the thickness of the gold nanoplate is 30nm.
[0055] S2. Detection of calcium chloride concentration:
[0056] (2-1) Drawing of standard curve: Prepare standard samples of calcium chloride aqueous solution with concentrations ranging from 5% to 50%, and evenly apply the standard samples of calcium chloride aqueous solution of various concentrations on the surface of the LSPR sensor. Use an ultraviolet spectrophotometer to measure the absorbance data of the standard samples on the surface of the LSPR sensor at 520nm. Draw a standard curve with absorbance as the ordinate and the calcium chloride concentration of the standard sample as the abscissa.
[0057] (2-2) Detection of the sample to be tested: The sample to be tested is uniformly coated on the surface of the LSPR sensor, and the absorbance data of the sample on the surface of the LSPR sensor is measured using an ultraviolet spectrophotometer. Then, the calcium chloride concentration of the calcium chloride solution sample to be tested is calculated according to the standard curve.
[0058] Example 2
[0059] S1. Preparation of LSPR sensor:
[0060] (1-1) Cleaning of FTO substrate: The FTO substrate was cleaned with acetone, isopropanol and ultrapure water for 30 min each, then dried with N2 gas and placed in an oven for 120 min to obtain a clean FTO substrate.
[0061] (1-2) Preparation of the modified solution: Dissolve thiol and ethylenediaminetetraacetic acid in ethanol to obtain a modified solution, wherein the concentration of thiol in the modified solution is 2 mM, and the concentration of ethylenediaminetetraacetic acid in the modified solution is 2 mM.
[0062] (1-3) Chemical modification of FTO substrate: The clean FTO substrate was immersed in the modification solution for 12 h. After being taken out, it was washed with ethanol and dried in a N2 atmosphere to obtain the chemically modified FTO substrate.
[0063] (1-4) Assembly of silver nanoplates: The chemically modified FTO substrate was placed in an electrolyte (a 0.05 M AgNO3 aqueous solution), and the metal nanoplates were assembled on the surface of the chemically modified FTO substrate by photoelectric induced deposition to obtain the LSPR sensor, wherein the distance between the xenon lamp and the FTO substrate was 30 cm, and the current density of the electrodeposition was 10 mA / cm 2 , the thickness of the silver nanoplate is 30nm.
[0064] S2. Detection of calcium chloride concentration:
[0065] (2-1) Drawing of standard curve: Prepare standard samples of calcium chloride aqueous solution with concentrations of 5%-50%, and evenly apply the standard samples of calcium chloride aqueous solution with different concentrations on the surface of LSPR sensor. Use UV spectrophotometer to measure the absorbance data of standard samples on the surface of LSPR sensor at 520nm. Draw the standard curve with absorbance as the ordinate and calcium chloride concentration of standard samples as the abscissa. Figure 2 shown.
[0066] (2-2) Detection of the sample to be tested: The sample to be tested is uniformly coated on the surface of the LSPR sensor, and the absorbance data of the sample on the surface of the LSPR sensor is measured using an ultraviolet spectrophotometer. Then, the calcium chloride concentration of the calcium chloride solution sample to be tested is calculated according to the standard curve.
[0067] Example 3
[0068] S1. Preparation of LSPR sensor:
[0069] (1-1) Cleaning of FTO substrate: The FTO substrate was cleaned with acetone, isopropanol and ultrapure water for 30 min each, then dried with N2 gas and placed in an oven for 120 min to obtain a clean FTO substrate.
[0070] (1-2) Preparation of the modified solution: Dissolve thiol and ethylenediaminetetraacetic acid in ethanol to obtain a modified solution, wherein the concentration of thiol in the modified solution is 2 mM, and the concentration of cyclodextrin in the modified solution is 2 mM.
[0071] (1-3) Chemical modification of FTO substrate: The clean FTO substrate was immersed in the modification solution for 12 h. After being taken out, it was washed with ethanol and dried in a N2 atmosphere to obtain the chemically modified FTO substrate.
[0072] (1-4) Assembly of copper nanoplates: The chemically modified FTO substrate was placed in an electrolyte (a 0.05 M Cu(NO3)2 aqueous solution), and the metal nanoplates were assembled on the surface of the chemically modified FTO substrate by photoelectric induced deposition to obtain the LSPR sensor, wherein the distance between the xenon lamp and the FTO substrate was 30 cm, and the current density of the electrodeposition was 10 mA / cm 2 , the thickness of the copper nanoplate is 30nm.
[0073] S2. Detection of calcium chloride concentration:
[0074] (2-1) Drawing of standard curve: Prepare standard samples of calcium chloride aqueous solution with concentrations ranging from 5% to 50%, and evenly apply the standard samples of calcium chloride aqueous solution of various concentrations on the surface of the LSPR sensor. Use an ultraviolet spectrophotometer to measure the absorbance data of the standard samples on the surface of the LSPR sensor at 520nm. Draw a standard curve with absorbance as the ordinate and the calcium chloride concentration of the standard sample as the abscissa.
[0075] (2-2) Detection of the sample to be tested: The sample to be tested is uniformly coated on the surface of the LSPR sensor, and the absorbance data of the sample on the surface of the LSPR sensor is measured using an ultraviolet spectrophotometer. Then, the calcium chloride concentration of the calcium chloride solution sample to be tested is calculated according to the standard curve.
[0076] Comparative Example 1
[0077] S1. Preparation of LSPR sensor:
[0078] (1-1) Cleaning of FTO substrate: The FTO substrate was cleaned with acetone, isopropanol and ultrapure water for 30 min each, then dried with N2 gas and placed in an oven for 120 min to obtain a clean FTO substrate.
[0079] (1-2) Preparation of modification solution: Dissolve thiol and ethylenediaminetetraacetic acid in ethanol to obtain a modification solution, wherein the concentration of thiol in the modification solution is 2 mM, and the concentration of crown ether in the modification solution is 2 mM.
[0080] (1-3) Chemical modification of FTO substrate: The clean FTO substrate was immersed in the modification solution for 12 h. After being taken out, it was washed with ethanol and dried in a N2 atmosphere to obtain the chemically modified FTO substrate.
[0081] (1-4) Assembly of gold nanoplates: The chemically modified FTO substrate was placed in an electrolyte (aqueous solution of HAuCl4 with a concentration of 0.1 M), and the metal nanoplates were assembled on the surface of the chemically modified FTO substrate by photoelectric induced deposition to obtain the LSPR sensor, wherein the distance between the xenon lamp and the FTO substrate was 30 cm, and the current density of the electrodeposition was 10 mA / cm 2 , the thickness of the gold nanoplate is 50nm.
[0082] S2. Detection of calcium chloride concentration:
[0083] (2-1) Drawing of standard curve: Prepare standard samples of calcium chloride aqueous solution with concentrations ranging from 5% to 50%, and evenly apply the standard samples of calcium chloride aqueous solution of various concentrations on the surface of the LSPR sensor. Use an ultraviolet spectrophotometer to measure the absorbance data of the standard samples on the surface of the LSPR sensor at 520nm. Draw a standard curve with absorbance as the ordinate and the calcium chloride concentration of the standard sample as the abscissa.
[0084] (2-2) Detection of the sample to be tested: The sample to be tested is uniformly coated on the surface of the LSPR sensor, and the absorbance data of the sample on the surface of the LSPR sensor is measured using an ultraviolet spectrophotometer. Then, the calcium chloride concentration of the calcium chloride solution sample to be tested is calculated according to the standard curve.
[0085] Comparative Example 2
[0086] S1. Preparation of LSPR sensor:
[0087] (1-1) Cleaning of FTO substrate: The FTO substrate was cleaned with acetone, isopropanol and ultrapure water for 30 min each, then dried with N2 gas and placed in an oven for 120 min to obtain a clean FTO substrate.
[0088] (1-2) Preparation of modification solution: Dissolve thiol and ethylenediaminetetraacetic acid in ethanol to obtain a modification solution, wherein the concentration of thiol in the modification solution is 2 mM, and the concentration of crown ether in the modification solution is 2 mM.
[0089] (1-3) Chemical modification of FTO substrate: The clean FTO substrate was immersed in the modification solution for 12 h. After being taken out, it was washed with ethanol and dried in a N2 atmosphere to obtain the chemically modified FTO substrate.
[0090] (1-4) Assembly of gold nanoplates: The chemically modified FTO substrate was placed in an electrolyte (HAuCl4 aqueous solution with a concentration of 0.05 M), and the metal nanoplates were assembled on the surface of the chemically modified FTO substrate by photoelectric induced deposition to obtain the LSPR sensor, wherein the distance between the xenon lamp and the FTO substrate was 15 cm, and the current density of the electrodeposition was 10 mA / cm 2 , the thickness of the gold nanoplate is 30nm.
[0091] S2. Detection of calcium chloride concentration:
[0092] (2-1) Drawing of standard curve: Prepare standard samples of calcium chloride aqueous solution with concentrations ranging from 5% to 50%, and evenly apply the standard samples of calcium chloride aqueous solution of various concentrations on the surface of the LSPR sensor. Use an ultraviolet spectrophotometer to measure the absorbance data of the standard samples on the surface of the LSPR sensor at 520nm. Draw a standard curve with absorbance as the ordinate and the calcium chloride concentration of the standard sample as the abscissa.
[0093] (2-2) Detection of the sample to be tested: The sample to be tested is uniformly coated on the surface of the LSPR sensor, and the absorbance data of the sample on the surface of the LSPR sensor is measured using an ultraviolet spectrophotometer. Then, the calcium chloride concentration of the calcium chloride solution sample to be tested is calculated according to the standard curve.
[0094] The measurement results of the above Examples 1-3, Comparative Example 1, and Comparative Example 2 were compared with the results of the conventional chemical detection method, and the specific results are shown in Table 1. The specific operation method of the conventional chemical detection method (EDTA titration method) is as follows: configure and calibrate the EDTA standard solution and the sodium hydroxide solution and calcium indicator of known concentration. Weigh a certain amount of liquid calcium chloride to be tested, dilute it to 20 times with water, stir evenly, weigh the diluted liquid to be tested, make the volume to 60mL, add a certain amount of sodium hydroxide solution to it, ensure that the pH is greater than 12, mix evenly, add 0.1g of calcium carboxylate indicator, titrate with EDTA standard solution to sky blue, record the volume of EDTA consumed and calculate the calcium chloride content.
[0095] Table 1 Test results of samples to be tested
[0096]
[0097] Sensitivity tests are performed on the gold nanoplates, silver nanoplates, and copper nanoplates of Examples 1 to 3, wherein the sensitivity test method is as follows: The refractive index sensitivity test of metals is usually related to the surface plasmon resonance (LSPR) technology. Sensor chips of different metals are mounted on a prism coupler. First, ensure good contact with the prism, and adjust the light source so that the light is coupled to the surface of the sensor chip through the prism. The position of the detector is adjusted so that the intensity of the reflected light can be detected, the LSPR response curve is analyzed, the change in the resonance angle is determined, the change in the resonance angle caused by the change in the refractive index is calculated, and the refractive index sensitivity of different metals is determined by the known refractive index change and the corresponding resonance angle change. Moreover, a numerical comparison is made with the sensitivity when gold nanoparticles, silver nanoparticles, and copper nanoparticles are used in the existing method, and the specific data are shown in Table 2 below.
[0098] The existing method of using gold nanoparticles, silver nanoparticles, and copper nanoparticles for detection is as follows: Nanoparticles are usually prepared by hydrothermal synthesis. In an autoclave, the FTO substrate is placed in a gasket, and salt solutions of different metal ions are added thereto to perform hydrothermal synthesis to prepare metal particles, which can be detected according to the method of metal nanoplates.
[0099] Table 2 Sensitivity data comparison
[0100]
[0101] From the data in Table 1 and Table 2 above, it can be seen that the Au nanoplate has the best effect in the comparison of the experimental results of the three metals, but considering the cost, the Ag nanoplate can achieve a significant effect. Compared with the prior art, the detection method of the present invention is sensitive, has a short detection time, can quickly complete the detection, and does not require complicated sample pretreatment, has high specificity and repeatability, is low in cost, is easy to mass produce and apply, and can achieve label-free, pollution-free, real-time, rapid and highly sensitive detection.
[0102] From the data in Table 2, we can see that the different morphologies and structures of metal nanoplates and metal nanoparticles have a certain influence on the resonant wavelength of LSPR. Nanoparticles are particles with spherical or polyhedral shapes, while nanoplates are materials with long strip shapes. The surface area of the nanoplate morphology is much larger than that of the nanoparticles. At the same time, the crystal planes and inter-crystalline spacing of the nanoplate morphology also contribute to the reaction. These characteristics enable the nanoplate to provide more reaction sites, thereby improving the catalytic efficiency. The nanoplate morphology has better stability than nanoparticles.
[0103] From the comparison of the data of Comparative Examples 1 and 2 and Example 1 in Table 1, it can be seen that the use of the metal nanoplate thickness size defined in the present invention and the light triggering distance defined in the present invention is more conducive to the accurate detection of calcium chloride.
[0104] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are exhaustively listed. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0105] For those skilled in the art, several modifications and improvements may be made without departing from the concept of the present invention, all of which belong to the protection scope of the present invention. The protection scope of the present invention shall be based on the attached claims.
Claims
1. A method for rapid detection of calcium chloride concentration based on localized surface plasmon resonance, characterized in that: The detection method is: S1. Preparation of LSPR sensor: The clean FTO substrate is placed in a modification solution for soaking, and after the soaking, the chemically modified FTO substrate is obtained by washing and drying; wherein the modification solution is an ethanol solution containing a thiol and a ligand compound, and the ligand compound is any one of cyclodextrin, crown ether, and ethylenediaminetetraacetic acid; The LSPR sensor is obtained by assembling metal nanoplates on the surface of a chemically modified FTO substrate using a photoelectric induced deposition method; S2. Detection of calcium chloride concentration: The calcium chloride solution sample to be tested is evenly coated on the surface of the LSPR sensor, an ultraviolet spectrophotometer is used to measure the absorbance data of the sample on the surface of the LSPR sensor, and then the calcium chloride concentration of the calcium chloride solution sample to be tested is calculated according to the standard curve.
2. A method for rapid detection of calcium chloride concentration based on localized surface plasmon resonance according to claim 1, characterized in that: In step S1, in the modified solution, the concentration of thiol is 2-10 mM, and the concentration of ligand compound is 1-5 mM.
3. A method for rapid detection of calcium chloride concentration based on localized surface plasmon resonance according to claim 1, characterized in that: In step S1, in the photoelectric induced deposition method, the light source used is a xenon lamp, and the light induction distance is 25-35 cm.
4. A method for rapid detection of calcium chloride concentration based on localized surface plasmon resonance according to claim 1, characterized in that: In step S1, in the photoelectric induced deposition method, the current density of the electrodeposition is 5-10 mA / cm 2 .
5. A method for rapid detection of calcium chloride concentration based on localized surface plasmon resonance according to claim 1, characterized in that: In step S1, the material of the metal nanoplate is gold, silver or copper, and the thickness of the metal nanoplate is 25-35 nm.
6. A method for rapid detection of calcium chloride concentration based on localized surface plasmon resonance according to claim 1, characterized in that: In step S1, in the photoelectric induced deposition method, the electrolyte used is HAuCl4 aqueous solution, AgNO3 aqueous solution or Cu(NO3)2 aqueous solution, and the concentration of the electrolyte is 0.04-0.05M.
7. A method for rapid detection of calcium chloride concentration based on localized surface plasmon resonance according to claim 6, characterized in that: The pH of the electrolyte is 4-5, and the temperature of the electrolyte is 60-80°C.
8. A method for rapid detection of calcium chloride concentration based on localized surface plasmon resonance according to claim 1, characterized in that: In step S2, when the localized surface plasmon resonance spectrometer performs detection, the absorbance of the sample to be tested is measured at a wavelength of 520 nm.
9. A method for rapid detection of calcium chloride concentration based on localized surface plasmon resonance according to claim 1, characterized in that: In step S1, the clean FTO substrate is treated by washing the FTO substrate with acetone, isopropanol and ultrapure water for at least 30 minutes each, then drying with N2 gas, and drying in an oven for at least 120 minutes to obtain a clean FTO substrate.
10. The method for rapid detection of calcium chloride concentration based on localized surface plasmon resonance according to claim 1, characterized in that: In step S1, the clean FTO substrate is soaked in the modification solution for 12-24 hours. After soaking, it is washed with ethanol and dried in a N2 atmosphere to obtain a chemically modified FTO substrate.
Citation Information
Patent Citations
Method for preparing Raman-enhanced substrate with silicon surface modified by silver nanoparticles
CN105386017A
Local plasma optical imaging ellipsometry biosensor and preparation method thereof
CN106323918A